Perbandinganantaratekniktwodot dengananalisis sefalometri pada pengukuran dimensi vertikal oklusi (Comparison between two dot technique with cephalometric analysis on the measurement of the vertical dimension of occlusion) - Muhammad Nurung; Moh. Dharmautama; Eri H. Jubhari; Eka Erwansyah (Journal of Dentomaxillofacial Science, 2014)
The vertical dimension can be described as a vertical height of the face. Practical knowledge about the physiologicalrest position is very important in determining the vertical dimension of occlusion (VDO) accurately. DeterminationVDO is one tough stage of prosthodontic treatment. There is no method or tool that can measure VDO accurately. Thisstudy can be used by dentists to help evaluate the results of VDO measurement performed by two dot technique, soconvincing dentists that the measurements are accurate. The distance was measured after the the two points on the tipof the nose and the tip of the chin assess, while DVO on the photo cephalometric measured by assessing the angle ofthe bispinal plane (SNA-SNP) with mandibular plane (Go-Gn), then OVD of cephalometric imaging was comparedwith compare the results of photo DVO cephalometric by two dots technique were measuring with Moyers standard.Based on research conducted at Dental Hospital University of Hasanuddin, there were obtained 20 samples that met the criteria as research subjects. Measuring DVO on the cephalometric photo, the mean value obtained on men20.214°and women 22.231°, insignificant statistically. It was concluded that the mean value of DVO corner was21.52°, still in the range of Moyers value with range 9-32°.